146 Prognostic significance of unexplained left ventricular hypertrophy in patients undergoing carpal tunnel surgery. (8th December 2021) - Porcari, Aldostefano; Pagura, Linda; Longo, Francesca; Sfriso, Enrico; Barbati, Giulia; Murena, Luigi; Longo, Emiliano; Ramella, Vittorio; Arnez, Zoran Marij; Rapezzi, Claudio; Merlo, Marco; Sinagra, Gianfranco
Abstract: Aims: Carpal tunnel (CT) syndrome is a recognized red-flag of cardiac amyloidosis (CA) and increased cardiovascular (CV) morbidity. We designed this study to characterize the CV profile of patients with CT syndrome at the time of first surgery and to identify high-risk presentations. Methods and results: We retrospectively reviewed 643 patients who underwent CT surgery between 2007 and 2019. Of them, 130 patients (77 years, 45% males, LVEF 62%) with available CV characterization within ±12 months from CT surgery were included. Abnormal loading conditions causing cardiac hypertrophy (LVH) were investigated to distinguish explained LVH (Ex-LVH) from unexplained LVH (Un-LVH). The primary outcome of the study was all-cause mortality. The secondary outcome measures were the occurrence of (i) new-onset heart failure (HF) or worsening HF requiring hospitalization (HHF) or (ii) pacemaker implantation. New-onset HF was defined as the development of HF signs and symptoms requiring an unplanned cardiologic examination or hospitalization. Median follow-up was 63 months [interquartile range (IQR): 30–95]. LVH was found in 65 (50%) patients, 33% of them presented Un-LVH. Compared to the others, Un-LVH patients were older (77, 75 vs. 70 years in Un-LVH, Ex-LVH, and non-LVH, respectively; P = 0.002), had higher rates of ECG-echo discrepancy (70%, 14.3% and 1.6%, respectively; P < 0.001) and of echocardiographic findings of CA (24%, 7%, and 0%, P < 0.001). Among Un-LVH patients, 9 (43%) experienced death and 7 (33%) developed HF at 3.8 and 2.4 years from CT surgery, respectively. Compared to the others, death and HF development rates were higher in Un-LVH patients both at unadjusted ( P = 0.01 and P = 0.02, respectively) and adjusted analysis for age, gender, and renal insufficiency ( P = 0.00038 and P = 0.050, respectively). Conclusions: At the time of CT surgery, Un-LVH was found in more than 30% of patients with LVH and 24% of them showed echocardiographic features suggesting an underdiagnosed CA. Un-LVH was associated with higher all-cause mortality and HF development.